Structures Congress 2020 2020
DOI: 10.1061/9780784482896.033
|View full text |Cite
|
Sign up to set email alerts
|

New Bridge Inspection Approach with Joint UAV and DIC System

Abstract: This research aims to develop a new bridge inspection approach using unmanned aerial vehicle (UAV) coupled with digital image correlation (DIC) system. The DIC system incorporating UAV images can measure displacements or strains by analyzing patterns of reference and deformed images. As part of this research, a commercially available UAV, DJI Matrice 210, was integrated with the DIC system using a 3D printed mounting plate, and the joint UAV-DIC system was utilized to inspect a timber bridge girder in the Stru… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
3
0

Year Published

2021
2021
2025
2025

Publication Types

Select...
3
2
1

Relationship

1
5

Authors

Journals

citations
Cited by 7 publications
(3 citation statements)
references
References 26 publications
0
3
0
Order By: Relevance
“…Another emerging imaging-based application with UAVs is the displacement/deformation measurement techniques of bridge structure, e.g., photogrammetric computer vision [9], [83], [89], [97], [146] and digital image correlation (DIC) [79], [92]- [95], [148]. Despite these imaging-based techniques, it is also worth mentioning the use of Laser Doppler Vibrometers (LDV) in UAVs as a non-contact sensor to measure bridge displacements [84]- [86].…”
Section: Concretementioning
confidence: 99%
“…Another emerging imaging-based application with UAVs is the displacement/deformation measurement techniques of bridge structure, e.g., photogrammetric computer vision [9], [83], [89], [97], [146] and digital image correlation (DIC) [79], [92]- [95], [148]. Despite these imaging-based techniques, it is also worth mentioning the use of Laser Doppler Vibrometers (LDV) in UAVs as a non-contact sensor to measure bridge displacements [84]- [86].…”
Section: Concretementioning
confidence: 99%
“…Most importantly, the safety of rope access inspectors is uncertain (1). To resolve these issues, bridge inspections using drones have been frequently adopted by many researchers (2)(3)(4)(5)(6)(7)(8)(9)(10)(11)(12)(13)(14). Particularly, drones can provide easier accessibility and straightforward maneuverability to the inspectors to record a high volume of videos and images for visual defect detection of a bridge.…”
mentioning
confidence: 99%
“…Although the drone-enabled inspection is a useful approach to identify the defects, the inherent limitation of the image analysis may impede the accurate quantification of the defects because of inaccurate and insufficient defect boundary information. Many studies have suggested various image processing techniques including pixel-based measurement (15), pattern recognition (16)(17)(18), and digital image correlation (7,(19)(20)(21). Especially, defect measurement using the pixel-based measurement technique (15) is regarded as a commonly used suitable technique to quantify specific defects such as spalling, efflorescence, and discoloration.…”
mentioning
confidence: 99%